Odpowiedzi

2010-04-09T15:31:44+02:00
A) -3,07x+2,132=4,281 /-2,132
-3,07x=2,149/:(-3,07)
x=-0,7

spr.
-3,07 * (-0,7) + 2,132 = 4,281
2,149+2,132=4,281
4,281=4,281


b) 6,42x -1,304= -8,366 / +1,304
6,42x=-7,062 /:6,42
x=-1,1

spr.
6,42 * (-1,1) - 1,304 = -8,366
-7,032 - 1,304 = -8,366
-8,366=-8,366

2010-04-09T15:32:52+02:00
A) -3,07x+2,132=4,281 /-2,132
-3,07x = 2,132 /:3,07
-x = 0,7 /*(-1)
x = -0,7

Spr.: -3,07*(-0,7)+2,132=4,281
2,149+2,132=4,281
4,281 = 4,281


b) 6,42x -1,304= -8,366 /+1,304
6,42x = -7,062 /: 6,42
x = -1,1

Spr.: 6,42*(-1,1) -1,304= -8,366
-7,04-1,304 = -8,366
-8,366 = -8,366

Proszę bardzo :)
2010-04-09T15:33:43+02:00
A) -3,07x+2,132=4,281
-3,07x=4,281-2,132
-3,07x=2,149/:(-3,07)
x=-0,7
spr.: -3,07*(-0,7)+2,132=4,281
-2,149=-2,149
L=P

b) 6,42x -1,304= -8,366
6,42x=-8,366+1,304
6,42x=-7,062/:6,42
x=-1,1
spr.:6,42*(-1,1) -1,304= -8,366
-8,366=-8,366
L=P